Dissemination Program in Improving Information Services to the Community in Bone District - Syamsiah Hasyim; Sofyang Sofyang; Khair Khalis Syurkati; Sumarni Sumarni (Jurnal Office, 2021)
Dissemination is a group of people or individuals who can obtain information through an activity, thus causing awareness and acceptance so that the information can be utilized. This study aims to determine the dissemination program implemented by the Department of Information Communication and Encryption in improving information services to the community in Bone Regency, using qualitative descriptive research methods. The research data was obtained by using interview, observation and documentation studies. Furthermore, data analysis techniques, namely, data collection, data reduction, data presentation and drawing conclusions. The results showed that, face to face contact, carry out socialization; by telephone, carrying out the “Hallo Bone” program; by Post, publish brochures and pamphlets as a medium for disseminating information; by Display, placing banners and billboards in certain places within the Bone Regency area; Selective dissemination of information, releasing android-based information service applications; publication publishes an information bulletin; media that is carried out using newspapers/newspapers, website www.bone.go.i, local Radio Suara Bone Adat, Matajang Local Television, and Facebook and Instagram Social Media.